Implementasi Teknik Motion Graphics pada Video Promosi Sanggar Senam Anamedy Menggunakan Metode Research and Development - Syahputra, Ahmad Sandi; Miftakul Amin; Ema Laila (Jurnal Teknologi Informatika Multimedia Digital, 2024)
In an increasingly competitive and modern business environment like today, motion graphic-based promotional videos are a means that can provide an advantage in attracting the attention of the target market. The ability to combine visual elements, moving text, and animation provides an additional dimension to brand communication. This article discusses how motion graphics can create powerful visual narratives, build emotion, and convey complex messages in a more concise and easy-to-understand way. In this study, the authors created a promotional video based on motion graphics as a means of promotion to attract public attention. The development method used is the Research and Development method with the PPE model or (Planning, Production, Evaluation). This method is very useful in conducting research so that it is more structured and in accordance with predetermined planning